Pattern of Coronary Artery Diseases in Patients Having Age Less Than 40 Years with Acute Coronary Syndrome - Muhammad Haidar Zaman, Naveed Yaqoob, Muhammad Ilyas, Falak Zeb, Fahad Khalid, Nawab Ali, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To assess the pattern of coronary artery diseases in patients older than 40 years with acute coronary syndrome. Material and methods: This cross-sectional study was conducted at the Department of Cardiology, Pakistan Institute Of Medical Sciences (PIMS), Pakistan.. A total of 130 patients presenting with the acute coronary syndrome were enrolled. The pattern of coronary artery diseases was assessed. Categorical variables were presented as frequencies and percentages, while numerical variables were presented as mean and SD. Results: The mean age of the patients in our study was 27.96±5.48 years. Most of the patients were male, accounting for 106 (81.5%). The most common factor was smoking 55.4% followed by hypertension 51.5%. Single vessel disease was a typical pattern presented in patients 37.7%. Three vessels disease was the second typical pattern observed in 22.3%. Conclusion: Smoking and hypertension are the leading causes of coronary artery diseases. Single vessel disease is the most common pattern in coronary artery disease patients younger than 40 years. Keywords: Acute coronary syndrome, Coronary artery disease, Pattern, Risk factors